The Influence of the Microbiome on Metastatic Colorectal Cancer - Cass, Samuel; White, Michael G. (Clinics in Colon and Rectal Surgery, 2023)
The microbiome (bacteria, viruses, and fungi) that exist within a patient's gastrointestinal tract and throughout their body have been increasingly understood to play a critical role in a variety of disease, including a number of cancer histologies. These microbial colonies are reflective of a patient's overall health state, their exposome, and germline genetics. In the case of colorectal adenocarcinoma, significant progress has been made in understanding the mechanism the microbiome plays beyond mere associations in both disease initiation and progression. Importantly, this improved understanding holds the potential to further identify the role these microbes play in colorectal cancer. We hope this improved understanding will be able to be leveraged in the future through either biomarkers or next-generation therapeutics to augment contemporary treatment algorithms through the manipulation of a patient's microbiome—whether through diet, antibiotics, prebiotics, or novel therapeutics. Here we review the role of the microbiome in the setting of patients with stage IV colorectal adenocarcinoma in both the development and progression or disease as well as response to therapeutics.
Keywords: colorectal adenocarcinoma; colorectal liver metastasis; colorectal carcinomatosis; gut microbiome